Capabilities Under Telecoupling: Human Well-Being Between Cash Crops and Protected Areas in North-Eastern Madagascar - Llopis, Jorge C.; Diebold, Clara L.; Schneider, Flurina; Harimalala, Paul C.; Patrick, Laby; Messerli, Peter; Zaehringer, Julie G. (Frontiers in Sustainable Food Systems, 2020)
Global change processes are increasing their pace and reach, leading to telecoupled situations, where distant factors come to outpace local determinants of land use change. Often, these dynamics drive agricultural intensification processes, with as yet unclear implications for the well-being of human populations living in the areas affected. This study explores how two key telecoupling dynamics affect local well-being in the biodiversity hotspot of Madagascar. It focuses on forest frontier landscapes, which are undergoing processes of agricultural intensification as a consequence of distant factors. Concretely, we look at how the recent establishment of two, largely externally funded, terrestrial protected areas, Masoala National Park and Makira Natural Park, and the ongoing price boom for two export cash crops, vanilla and clove, have influenced the well-being of local populations in the country’s north-east. We present data from eight focus group discussions conducted in four villages located on the periphery of the two protected areas. Drawing on the ‘capabilities approach’, we identify the key components of the local understanding of well-being, lay out the interconnections between these components, and explore how the two telecoupling processes explored affect well-being dynamics. Our findings reveal that well-being components present bundle characteristics, where increases or decreases in one component lead to parallel increases or decreases in a set of them. We further ascertain that telecoupling processes might lead to trade-offs between well-being components. These findings highlight the need for a holistic understanding of human well-being when planning protected areas, and when designing governance mechanisms to steer local landscapes under intense cash crop price fluctuations towards sustainable outcomes.